PATH-04. LEPTOMENINGEAL DISEASE IN PATIENTS WITH HISTONE-MUTANT GLIOMAS. (12th November 2021) - Diaz, Maria; Correia, Carlos Eduardo Silva; Lin, Andrew; Miller, Alexandra; Pentsova, Elena
Abstract: INTRODUCTION: The 2016 WHO classification describes a subtype of midline gliomas harboring histone 3 (H3) K27M mutations, and the upcoming 2021 edition may include a new subtype of hemispheric diffuse gliomas with H3 G34R/V mutations. Since we began to perform molecular profiling at Memorial Sloan Kettering Cancer Center (MSKCC) we have observed an increased prevalence of leptomeningeal disease (LMD) in this population. However, the incidence and clinical behavior of LMD has not been well defined. METHODS: This is a retrospective study of patients with H3-mutant gliomas at MSKCC diagnosed from 01/2012 to 02/2021, either by tumor biopsy or by cerebrospinal fluid (CSF). Histone mutations were identified through next-generation sequencing (NGS). RESULTS: We found 40 patients (pts) harboring H3 mutations (K27M mutations in 31 pts, G34R/V in 8, and both in one), with 2/40 (5%) mutations identified through CSF NGS only and rest in tumor tissue. Median age was 20.5 years (4-70); 25 were male. Tumor location was midline for K27M-mutant tumors (thalamus [N=15], brainstem [N=10], spine [N=5], pineal gland [N=1]) and hemispheric for G34R/V-mutant tumors; tumor with both mutations was thalamic. LMD was diagnosed in 22/40 (55%) pts radiographically, including 19/31 (61%) of K27M-mutant pts and 3/8 (38%) of G34R/V-mutant pts (patient with both mutations did not develop LMD). At analysis, 10 patients remain alive. Median time from diagnosis to LMD was 8.8 months (0-44.4), with median OS of 6.5 months (0.3-34) after LMD diagnosis. CONCLUSION: More than half of patients with histone-mutant gliomas develop LMD, including over a third of patients with G34R/V mutations. Neuroaxis imaging should be performed in conjunction with CSF studies in histone-mutant gliomas. Besides, CSF NGS represents an important tool to identify molecular profile of tumors when biopsy is not feasible or there is limited tissue for analysis.